1992
DOI: 10.1002/art.1780350313
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of osteophyte formation in hyperglycemic patients with type II diabetes mellitus and knee osteoarthritis

Abstract: Objective. Since insulin is a potent growth factor for connective tissue, the present study was designed to investigate whether radiographic features of knee osteoarthritis (OA) in patients with poorly controlled, insulin-resistant type I1 diabetes mellitus differ from those in nondiabetic controls with knee OA.Methods. Radiographs from 25 female patients with diabetes and knee OA were compared with those from 48 female controls who were similar with respect to age, weight, and duration of OA symptoms.Results.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…These 5 prospective cohort studies involved much higher number of 83 857 subjects compared with the 2782 subjects involved in the positive studies with prospective cohort design (table 2). Within these five prospective cohort studies, four reported negative associations between DM and OA 9 12 13 33…”
Section: Resultsmentioning
confidence: 99%
“…These 5 prospective cohort studies involved much higher number of 83 857 subjects compared with the 2782 subjects involved in the positive studies with prospective cohort design (table 2). Within these five prospective cohort studies, four reported negative associations between DM and OA 9 12 13 33…”
Section: Resultsmentioning
confidence: 99%
“…Tumor necrosis factor-alpha (TNFα) and interleukin (IL)-1β from lipopolysaccharide-stimulated macrophages are lower in diabetic mice compared to control mice36. In a small case-control study, subchondral sclerosis and osteophytes on knee radiography were less common in subjects with diabetes compared to controls matched by age, weight, and duration of OA symptoms, suggesting that a diabetes state may attenuate the chondro- and osteo-genesis required for osteophyte formation in OA37.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the phenotypic appearance of radiographic knee osteoarthritis is different in patients with diabetes than in those without diabetes, with the patients with diabetes exhibiting less osteophytosis. 41 We speculated that the difference was due to less effect of insulin on new bone formation in osteoarthritis joints of patients with diabetes. Our study suggests a racial difference in the phenotype of radiographic knee osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%